Fungal Colitis by Paracoccidioides brasiliensis: a case report - Carlos José Galeazzi; Cássia Fernanda Estofolete; Antônio Carlos Soares de Moraes Filho; Anderson Lubito Simoni; Francisco de Assis Gonçalves-Filho; João Gomes Netinho (Journal of Coloproctology, 2011)
Paracoccidioidomycosis (PBM) is an infection caused by a dimorphic fungus called Paracoccidioides brasiliensis. It occurs in Latin America, with incidence of 1 to 3 per 100,000 inhabitants in endemic areas. The digestive tract is usually not affected, but when it occurs, it may lead to events similar to colorectal neoplasm and inflammatory bowel disease (IBD). This is a case report of a 68-year-old female patient, with diarrhea without blood or mucus for 6 months, weight loss of 8 kg over the period. Abdominal ultrasonography showed some mass in the right colon, suggestive of cancer and liver perihilar lymph node. Colonoscopy showed lesions suggestive of Crohn's disease. Biopsy showed chronic granulomatous colitis of fungal etiology: Paracoccidioidomycosis. The patient did not tolerate oral treatment with itraconazole and subsequently sulfadiazine, requiring hospital admission for the treatment with amphotericin B. The presence of Paracoccidioidomycosis in the digestive tract may be associated with bloody diarrhea, mucus, rectal hemorrhage, abdominal pain, malabsorption syndrome. Histopathological studies show the fungus and a chronic inflammatory infiltrate and granulation tissue. The differential diagnoses are tuberculosis, colorectal cancer and inflammatory bowel disease. The treatment is oral antifungal (itraconazole, sulfadiazine) or intravenous (amphotericin B) based. The case has caused diagnostic confusion between colon cancer (clinical and US) and Crohn's disease (colonoscopy). Paracoccidioidomicose (PBM) é uma infecção causada por um fungo dimórfico: Paracoccidioides brasiliensis. Ocorre na América Latina, com incidência de 1 a 3 por 100.000 habitantes em áreas endêmicas. O acometimento do trato digestivo é infrequente, sendo que pode levar a manifestações semelhantes à neoplasia colorretal e doença inflamatória intestinal (DII). Relatamos o caso da paciente feminina, 68 anos, com diarreia sem sangue ou muco há seis meses, com perda ponderal de 8 kg no período. Ultrassom abdominal evidenciou massa em cólon direito sugestiva de neoplasia e linfonodomegalia peri-hilar hepática. A colonoscopia evidenciou lesões sugestivas de doença de Crohn. A biopsia mostrou colite crônica granulomatosa de etiologia fúngica: Paracoccidioidomicose. A paciente não tolerou tratamento oral com itraconazol e, posteriormente, sulfadiazina. Necessitou de internação para tratamento com anfotericina B. O acometimento da PBM no trato digestivo pode cursar com diarreia muco-sanguinolenta, retorragia, dor abdominal e síndrome de má absorção. O estudo histopatológico mostra o fungo e um infiltrado inflamatório crônico com tecido de granulação. Os diagnósticos diferenciais são tuberculose, câncer colorretal e doença inflamatória intestinal. O tratamento é feito com antifúngicos orais (itraconazol, sulfadiazina) ou endovenosos (anfotericina B). O caso levou à confusão diagnóstica entre câncer de cólon (US e quadro clínico) e doença de Crohn (colonoscopia).